A Compact Dual-band MIMO Antenna for 5G Mobile Communications - Jianxun Su; Zhengyu Dai; Jianhe Du; Jiayong Yu; Zeqiang Chen; Zengrui Li (Applied Computational Electromagnetics Society Journal (ACES), 2019)
In this paper we propose a compact dualband MIMO antenna for 5G mobile communications. Its element is a dual-band monopole working at 3.4 GHz and 4.9 GHz. In order to cover the commercial 5G communication band of sub-6 GHz (3.3-3.6 GHz and 4.8-5.0 GHz), an inverted L-shaped strip is added on the ground of the monopole to achieve a band-notch of S11 at 3.4 GHz and a quasi-directional radiation pattern. The proposed MIMO antenna has a compact size of 50*50*0.8mm3 and it’s composed of four improved monopoles mentioned above with mutually orthogonal placement. Long strips are loaded on the ground layer and antenna layer to obtain a better port isolation at 3.3- 3.6 GHz. The measured results show that the reflection coefficient (Sii) of the MIMO antenna is less than -10 dB at the lower band and less than -20dB at the higher band. Its -10dB-bandwidth covers the band of 3.3-5.8 GHz and the mutual coupling (Sij) between ports keeps lower than -20dB within the dual-band. The envelope correlation coefficients (ECC) of the MIMO antenna are also measured and they’re below 0.01. A channel model is used to calculate the MIMO channel capacity and the results show this MIMO channel performs best at 5 GHz.